1999
DOI: 10.1006/aphy.1999.5923
|View full text |Cite
|
Sign up to set email alerts
|

Global Properties of Warped Solutions in General Relativity

Abstract: Assuming the four-dimensional space-time to be a general warped product of two surfaces we reduce the four-dimensional Einstein equations to a two-dimensional problem which can be solved. All global vacuum solutions are explicitly constructed and analysed. The classification of the solutions includes the Schwarzschild, the (anti-)de Sitter, and other well-known solutions but also many exact ones whose detailed global properties to our knowledge have not been discussed before. They have a natural physical inter… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
51
0

Year Published

1999
1999
2005
2005

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 37 publications
(53 citation statements)
references
References 19 publications
2
51
0
Order By: Relevance
“…As already mentioned the pseudo-Schwarzschild metric (2) is locally the only so (2, 1)-invariant solution of the Einstein field equations in the vacuum ‡ . This is the static solution found in [12] and also, in the context of warped solutions, in [10]. The more physically interesting gravitational field, generated by a distribution of matter described by an energy-momentum tensor T µν and reducing in the vacuum to the previous one, is given by…”
mentioning
confidence: 54%
“…As already mentioned the pseudo-Schwarzschild metric (2) is locally the only so (2, 1)-invariant solution of the Einstein field equations in the vacuum ‡ . This is the static solution found in [12] and also, in the context of warped solutions, in [10]. The more physically interesting gravitational field, generated by a distribution of matter described by an energy-momentum tensor T µν and reducing in the vacuum to the previous one, is given by…”
mentioning
confidence: 54%
“…where K = 1, 0, −1 for spherical, planar, or hyperbolic reductions, respectively [33]. Λ is the four-dimensional cosmological constant, and κ > 0 is the inverse gravitational constant in four dimensions.…”
Section: The Actionmentioning
confidence: 99%
“…It can be shown that its variation leads to the same EOM as the ones from the original 4D action when the symmetry is introduced there. This point is nontrivial as witnessed by the reduced action resulting from warped metrics in Einstein gravity [16]. From the Gowdy line-element alone it is not clear why to define as dilaton fields X and Y as in (15).…”
Section: Gowdy Modelmentioning
confidence: 99%